FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SAFETY DRIVING PADA PENGEMUDI BUS RAPID TRANSIT TRANS SEMARANG KORIDOR I - Dimas Adiyanto; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2021)
Safety driving is a way of driving based on safety standards by implementing safe driving behavior that is to anticipate dangerous situations and reduce the risk of accidents and traffic problems. The majority of traffic accidents occur due to human error, this is caused by lack of driving discipline and drivers' ignorance of safe driving procedures. Therefore we need an approach to determine the driving behavior in the causes of accidents that occur caused by human error. The purpose of the study to analyze the relationship between individual characteristics, predisposing, enabling, and reinforcing factors with safety driving behavior in Bus Rapid Transit Trans Semarang corridor I drivers. The research used quantitative research by analytic survey with cross sectional study approach. The population of this study is all the drivers of the Bus Rapid Transit Trans Semarang Corridor 1 with total 43 people. The sample in this study used a total sample population, the sample in this study amounted to 43 people. Data in this study were colleted by using an angket. Based on the chi-square statistical test, the result shows the variables that related with safety driving behaviour are knowledge (p-value = 0.010), attitude (p-value = 0.021), safety driving training (p-value = 0.008). and variables unrelated to the safety driving behaviour is the working period (p-value = 0.098), driving duration (p-value - 0.988), rest time (p-value = 0.069, vehicle condition (p-value = 0.094), motivation/family support (p-value = 0.780). This research suggests providing safety driving training to all drivers of Bus Rapid Transit Trans Semarang to increase driver knowledge and awareness of driving safety, and the driver's abilities and skills.